T36 ALGEBRA TOOLKIT B
■
Working with Expressions
example
7
Recognizing Perfect Squares
Factor each trinomial.
(a) (b)
Solution
(a) Here and , so . Since the middle term is 6x,
the trinomial is a perfect square. By the Perfect Square Formula we have
(b) Here and , so . Since the middle term is
, the trinomial is a perfect square. By the Perfect Square Formula we have
■ NOW TRY EXERCISES 41 AND 47 ■
When we factor an expression, the result can sometimes be factored further. In
general, we first factor out common factors, then inspect the result to see whether it
can be factored by any of the other methods of this section. We repeat this process
until we have factored the expression completely.
4x
2
- 4xy + y
2
= 12x - y2
2
- 4xy
2AB = 2
#
2x
#
y = 4xyB = yA = 2x
x
2
+ 6x + 9 = 1x + 32
2
2AB = 2
#
x
#
3 = 6xB = 3A = x
4x
2
- 4xy + y
2
x
2
+ 6x + 9
example
8
Factoring an Expression Completely
Factor each expression completely.
(a) (b)
Solution
(a) We first factor out the power of x with the smallest exponent.
Common factor is
Factor as a Difference of Squares
(b) We first factor out the powers of x and y with the smallest exponents.
Common factor is
Factor as a Difference of Squares
Factor as a Difference of Squares
■ NOW TRY EXERCISES 49 AND 53 ■
x
2
- y
2
= xy
2
1x
2
+ y
2
21x + y21x - y2
x
4
- y
4
= xy
2
1x
2
+ y
2
21x
2
- y
2
2
xy
2
x
5
y
2
- xy
6
= xy
2
1x
4
- y
4
2
x
2
- 4 = 2x
2
1x - 2 21x + 2 2
2x
2
2 x
4
- 8x
2
= 2x
2
1x
2
- 42
x
5
y
2
- xy
6
2x
4
- 8x
2
Solution
(a) Using the Difference of Squares Formula with and , we have
(b) We use the Difference of Squares Formula with and .
■ NOW TRY EXERCISES 33 AND 37 ■
1x + y2
2
- z
2
= 1x + y - z21x + y + z2
B = zA = x + y
A
2
- B
2
= 1A - B21A + B 2
4x
2
- 25 = 12x2
2
- 5
2
= 12x - 5212x + 52
B = 5A = 2x